2021
DOI: 10.12659/msm.926760
|View full text |Cite
|
Sign up to set email alerts
|

Connection Between CDC20 Expression and Hepatocellular Carcinoma Prognosis

Abstract: Background Hepatocellular carcinoma (HCC) occurs frequently in China, with high morbidity and mortality. Cell division cycle 20 homolog ( CDC20 ) is reportedly related to many cancers. In this study, we discuss a potential link of CDC20 expression to HCC patients’ prognoses. Material/Methods Quantitative real-time polymerase chain reaction (qRT-PCR) was performed to assess CDC20 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…It is the target of the spindle assembly checkpoint (SAC) and the key cofactor of the anaphase-promoting complex or cyclosome (APC/C) E3 ubiquitin ligase, thus regulating APC/C ubiquitin activity on specific substrates for their subsequent degradation by the proteasome (62). CDC20 is overexpressed in tumor cells and acts as a poor prognostic factor in multiple cancers (63,64). It further increased after radiation and has been reported to increase radiation resistance via regulating B-cell lymphoma-2 (Bcl-2)/Bcl-2-associated X protein (Bax), forkhead box proteins O1 (FoxO1), or myeloid cell leukemia sequence 1 (Mcl-1)/p-CHK1 in different cancer types (65)(66)(67).…”
Section: Cdc20mentioning
confidence: 99%
“…It is the target of the spindle assembly checkpoint (SAC) and the key cofactor of the anaphase-promoting complex or cyclosome (APC/C) E3 ubiquitin ligase, thus regulating APC/C ubiquitin activity on specific substrates for their subsequent degradation by the proteasome (62). CDC20 is overexpressed in tumor cells and acts as a poor prognostic factor in multiple cancers (63,64). It further increased after radiation and has been reported to increase radiation resistance via regulating B-cell lymphoma-2 (Bcl-2)/Bcl-2-associated X protein (Bax), forkhead box proteins O1 (FoxO1), or myeloid cell leukemia sequence 1 (Mcl-1)/p-CHK1 in different cancer types (65)(66)(67).…”
Section: Cdc20mentioning
confidence: 99%
“…In terms of CDC20, CCNB1, and PLK1, they also have been indicated as potential prognostic markers in carcinoma patients as well. 25 , 26 , 27 For instance, CDC20 is upregulated in tumor tissue compared to non‐tumor tissue from HCC patients, also increased CDC20 is associated with lymph node metastasis, advanced pTNM stage, and reduced OS in HCC patients. 25 Besides, CCNB1 is reported to be upregulated in tumor tissue from HCC patients, and enhanced CCNB1 is related to declined DFS and OS in HCC patients as well.…”
Section: Discussionmentioning
confidence: 99%
“… 25 , 26 , 27 For instance, CDC20 is upregulated in tumor tissue compared to non‐tumor tissue from HCC patients, also increased CDC20 is associated with lymph node metastasis, advanced pTNM stage, and reduced OS in HCC patients. 25 Besides, CCNB1 is reported to be upregulated in tumor tissue from HCC patients, and enhanced CCNB1 is related to declined DFS and OS in HCC patients as well. 26 Moreover, PLK1 is related to reduced DFS and OS in ovarian carcinoma patients, also it is independently associated with shorter OS by multivariate Cox's regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Results of this study revealed that BUB1 and CDC20 had significantly higher expression levels in platinum-sensitive samples than that of platinum-resistant in both two GEO datasets. Accumulating evidence indicates that there is a strong link between abnormal upregulation of CDC20 and various types of tumors [ 41–43 ]. CDC20 knockdown was shown to sensitize cancer cells to chemotherapy and radiation therapy [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%